Juvenile chondrodermatitis nodularis helicis. - Zaman, M.; Torchia, D. (European Journal of Pediatric Dermatology, 2019)
Chondrodermatitis nodularis helicis, probably better defined as chondrodermatitis nodularis auricularis (1), is a chronic and benign condition of the external ear that most commonly affects older adults. CNH can exceptionally occur in the pediatric age, with six cases (four males, two females, average age 12.7 years, range 8-16) previously reported in the English literature to date (2, 3, 4, 5, 6). Interestingly, three cases were associated with stigmata of connective tissue disease (juvenile dermatomyositis (6), rheumatoid nodule (4) and subacute cutaneous lupus erythematosus (4), possibly reflecting impairment of the microcirculation as a pathogenic factor, but maybe simply implying a publication bias. In the four cases where treatment was mentioned, surgical excision was carried out and proved successful (2, 3, 5, 6). To our knowledge, the present case represents the seventh reported instance of juvenile CNH and confirms that surgical excision still represents its most effective treatment.